Three known species of the genus Parahadronchus – First report from Mizoram, India - Sushilkumar, S.; Mexico, S.; Mohilal, N. (International Journal of Scientific Research in Biological Sciences, 2021)
Mononchs play a vital role in reducing phytophagous nematode population. The present study deals with the diversity of Parahadronchus in Mizoram. Various soil samples were collected from different parts of Mizoram along with the GPS location. Upon processing and examination, three known species of the genera Parahadronchus were found, viz., Parahadronchus siroii, Parahadronchus marami and Parahadronchus shakili. P. siroii is distinguishable from P. shakili in its smaller body, short oesophagus, lesser number of vulval papillae, small lip, etc. P. marami has narrower buccal cavity, thinner body with three subventral denticles. P. shakili has larger body, broader buccal cavity with 3-6 subventral teeth.